The Determinants of Active Instruction at Indonesian Elementary Schools as Perceived by Teachers - Kaluge, Laurens; Yulianti; Fernandez, Bernadetha Aprilia; Prathiwi, Natalia (International Conference on Elementary Education, 2022)
Considerable studies on learning so far had been much on limited terms of learning outcomes, curriculum, theories of learning, teaching methods and teacher competencies. Only a handful information on school and classroom contexts, and relevant expressions of teacher perceptions were provided to explain the instructional process. Therefore, this study aimed at examining the effectiveness of constructs on active instruction at the elementary schools. This research was a causal-correlational type using a sample of 1026 elementary school teachers who spread across six provinces, namely West and Central Java, West and East Nusatenggara, South Celebes, and South Borneo. Data accessed from the MGPBE program sponsored by the European Union. Statistical modeling through multiple regression analysis, estimated effect size and determinant coefficients were calculated and used. It found that there were discrepancies in the picture of active instruction between schools in the mainland and outside of Java except for NTB; related constructs on classrooms were significant and had an effect of about fifty per cent, while the institutional level constructs were not significant, the geographical disparity between locations had significant effects although of around three pe cent. These findings had an impact on education policies to determine strategies for improving instruction at elementary school classrooms.